Design of a Portable Power Plant Using Solar and Wind Energy with Hybrid Charge Control Method - Vrathama, Brenanda Kristian; Silalahi, Lukman Medriavin (Universitas Raharja, 2025)
New Renewable Energy is an environmentally friendly solution for electricity generation, particularly through the utilization of wind and solar energy. In Indonesia, which has a tropical climate, both energy sources can reduce dependence on fossil fuels and carbon emissions. This research aims to design a portable power plant that integrates solar and wind energy using the Hybrid Charge Control method.[1] Testing was conducted at two different locations: Pantai Indah Kapuk 2 (PIK2) and VI Rusun Ujung Menteng. The results showed that in PIK2, the solar power plant reached a peak power of 3.459 W at 1:00 PM, while the wind source produced a peak power of 0.66 W at 5:00 PM. At the Rusun Ujung Menteng location, the highest recorded power from the solar panel was 3.048 W at 2:00 PM, and the wind source reached 0.82 W at 5:30 PM. The use of a DC motor in this system increased the voltage to 4 Volts but also presented issues requiring attention in torque management and cable material selection. The Charge Control method was applied to equalize the battery voltage at a level of 12.4 V. The researchers demonstrated the significant potential of portable renewable energy-based power plants for sustainable energy needs in Indonesia.